Question

(7x²)³ x ⁻⁴

218

likes1092 views

Gene

4.5

92 Answers

First, simplify the expression (7x^2)^3 :

(7x^2)^3 = 7^3 \cdot (x^2)^3 = 343x^6

Then, combine it withx^{-4} using the property of exponents a^m \cdot a^n = a^{m+n} :

343x^6 \cdot x^{-4} = 343x^{6-4} = 343x^2

So the final simplified expression is:

343x^2

Then, combine it with

So the final simplified expression is:

Frequently asked questions (FAQs)

Math question: What's the factored form of 6x^2 − 11x − 10?

+

Question: What is the derivative of f(x) = √(3x^2 + 5x) with respect to x?

+

Math Question: Find the 4th derivative of f(x) = 3x^5 - 2x^3.

+

New questions in Mathematics